All-cause mortality in people with cirrhosis compared with the general population: a population-based cohort study - Fleming, Kate M.; Aithal, Guruprasad P.; Card, Tim R.; West, Joe (Wiley, 2012)
Background: Mortality due to cirrhosis has tripled over the last 30 years in the UK. However, we lack adequate, contemporary, population-based estimates of the excess mortality patients who are at risk compared with the general population. Aim: To determine the overall survival in patients with cirrhosis compared with the general population taking into account the effects of severity and aetiology of disease and comorbidity. Methods: In a cohort study, we identified 4537 people with cirrhosis and a control cohort of 44 403 patients, matched by age, sex and general practice from the UK General Practice Research Database between June 1987 and April 2002. Results: Patients with compensated cirrhosis had a nearly five-fold [hazard ratio (HR) 4.7, 95% confidence interval (CI) 4.4–5.0] increased risk of death, while those with decompensated cirrhosis had a near 10-fold (HR 9.7, 95% CI 8.9–10.6) increased risk compared with the general population. Alcoholic cirrhosis conferred a worse prognosis than non-alcohol-related cirrhosis both in the first year following diagnosis and subsequently. Conclusion: Having a diagnosis of cirrhosis confers a substantial increased mortality risk compared with the general population, even for those with compensated disease, with 5-year survival between that seen for breast and colorectal cancer.